Activation of ILC2s through constitutive IFNγ signaling reduction leads to spontaneous pulmonary fibrosis - Natsuko Otaki; Yasutaka Motomura; Tommy Terooatea; S. Thomas Kelly; Miho Mochizuki; Natsuki Takeno; Shigeo Koyasu; Miu Tamamitsu; Fuminori Sugihara; Junichi Kikuta; Hideya Kitamura; Yoshiki Shiraishi; et al. (Nature Communications, 2023)
Abstract Pulmonary fibrosis (PF), a condition characterized by inflammation and collagen deposition in the alveolar interstitium, causes dyspnea and fatal outcomes. Although the bleomycin-induced PF mouse model has improved our understanding of exogenous factor-induced fibrosis, the mechanism governing endogenous factor-induced fibrosis remains unknown. Here, we find that Ifngr1 -/- Rag2 -/- mice, which lack the critical suppression factor for group 2 innate lymphoid cells (ILC2), develop PF spontaneously. The onset phase of fibrosis includes ILC2 subpopulations with a high Il1rl1 (IL-33 receptor) expression, and fibrosis does not develop in ILC-deficient or IL-33-deficient mice. Although ILC2s are normally localized near bronchioles and blood vessels, ILC2s are increased in fibrotic areas along with IL-33 positive fibroblasts during fibrosis. Co-culture analysis shows that activated-ILC2s directly induce collagen production from fibroblasts. Furthermore, increased IL1RL1 and decreased IFNGR1 expressions are confirmed in ILC2s from individuals with idiopathic PF, highlighting the applicability of Ifngr1 -/- Rag2 -/- mice as a mouse model for fibrosis research.